Steroid responsive cardiomyopathy. - Probert, C; Pavord, I; Roland, J (1990)
Heart disease responsive to steroids is well described in many disorders, including sarcoidosis, systemic lupus erythematosus, polyarteritis nodosa, myocarditis and Churg-Strauss syndrome. The underlying disorder is often obvious and the response is usually slow. We describe a woman who had severe left ventricular failure, cardiac dilatation and pericardial effusion which were rapidly rectified by steroid therapy. Steroid withdrawal led to recurrence of signs, which were reversed by recommencing steroids. The aetiology was not determined.